2009
DOI: 10.1596/28276
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis of Aquaculture Value Chain in Northeast Vietnam and Nigeria

Abstract: The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judgment on the part of The World Bank concerning the legal status of any territory or the endorsement or acceptance of such boundaries. Rights and PermissionsThe material in this publication is copyrighted. Copying and/or transmitting portions or all of this work without permission may be a violation of applicable law. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 10 publications
0
32
1
1
Order By: Relevance
“…In Nigeria, a cultural bias against women interacting with male extension agents limits women's access to skill development services (Veliu et al . ).…”
Section: Dynamics Mediating Productivitymentioning
confidence: 97%
See 1 more Smart Citation
“…In Nigeria, a cultural bias against women interacting with male extension agents limits women's access to skill development services (Veliu et al . ).…”
Section: Dynamics Mediating Productivitymentioning
confidence: 97%
“…Meanwhile in Nigeria, Veliu et al . () found that women's domestic responsibilities meant few could operate time‐consuming fish hatcheries and so had to rely on poor quality commercially obtained fry for their ponds.…”
Section: Dynamics Mediating Productivitymentioning
confidence: 99%
“…Furthermore, gender issues, like the opportunities for increased women participation and responsibility in the labor market through aquaculture development may gain more prominence. However, this seems to primarily have been an issue for developing countries (Veliu et al 2009;Ndanga et al 2013).…”
Section: Effects On Cultural Fabric and Other Social Aspectsmentioning
confidence: 99%
“…C'est le cas au Nigéria, 20% et 40% respectivement dans les Etats de Kaduna et de Lagos. Au Srilanka et au Bangaldesh, les femmes représentent respectivement 30% et 60% des pisciculteurs (FAO, 2012 ;Veliu et al, 2009). Ces données suggèrent que dans certaines régions de la Côte d'Ivoire comme dans certains pays, les contraintes liées aux barrières sociétales, aux moeurs et aux coutumes ont pu être atténuées.…”
Section: Production Des Fermes Piscicoles Appartenant Aux Femmesunclassified